MHD Modeling of the Plasma Interaction With Io's Asymmetric Atmosphere. Issue 11 (21st November 2018) - Blöcker, Aljona; Saur, Joachim; Roth, Lorenz; Strobel, Darrell F.
Abstract: Io's atmosphere, with an average equatorial column density of ≥10 20  m −2, exhibits significant density variations with latitude and longitude. We apply a 3‐D magnetohydrodynamic model to investigate the effects of atmospheric asymmetries, both locally from volcanic plumes and globally, on the plasma and magnetic field environment of Io. The model takes into account collisions between ions and neutrals, plasma production and loss due to electron impact ionization and dissociative recombination, and the ionospheric Hall effect. Our simulation results show that volcanic plumes influence the plasma interaction locally, generating Alfvén winglets within Io's global Alfvén wing. Signals from individual plumes can however barely be probed by magnetic field measurements during spacecraft flybys at Io. In contrast, the surface number density, scale height, the longitudinal and latitudinal variations of the global atmosphere are crucial factors for modeling and understanding magnetic field and plasma perturbations. Comparing our model results with the magnetic field data from the I24 and I27 flybys of the Galileo spacecraft, we find that the measured perturbations can be primarily caused by the plasma interaction with the longitudinally asymmetric atmosphere. This implies that a significant magnetic induction signal from a partially molten magma ocean is not necessarily required to explain the Galileo magnetometer data. Key Points: A near‐surface magma ocean is not necessarily required to explain the Galileo MAG data Atmospheric asymmetries crucially affect Io's magnetic field and plasma environment Volcanic plumes in Io's global atmosphere generate Alfvén winglets within Io's global Alfvén wings